Aspects of ecological anatomy of Traganum nudatum Del. (Amaranthaceae) from the Northeast of the Algerian Sahara - Kherraze, Mohamed Elhafed; Belhamra, Mohamed; Grigore, Marius-Nicuşor (Acta Biologica Szegediensis, 2018)
This study focuses on the anatomical strategies developed by the Traganum nudatum Del., prevalent in the Algerian Sahara, particularly in the region of Oued Righ, which allows to this species to survive in a harsh environment (aridity and salinity). The anatomical structure of this species was studied using fresh materials (roots, stems and leaves). These materials have been collected from several individuals in different saline habitats. Some interesting features such as successive cambia phenomenon, calcium oxalate crystals, Kranz anatomy (salsoloid subtype), succulence, low stomata density, low stomata index, the presence of the papillae, paracytic stomata and other structures have been noticed. We can conclude that the ecological significance of evidenced adaptations by T. nudatum is supported in this article by the analysis of adaptations of other species belonging either to the Amaranthaceae or to other botanical families; and that this adaptation has no link with botanical families. In these species, the key adaptation is the ability to maintain growth processes and water saving under difficult living conditions (high summer temperatures or salty soils), regardless of the evolutionary level of the taxon.